Public intervention in farmer-managed irrigation systems - International Irrigation Management Institute; Ministry of Water Resources, Nepal (International Irrigation Management Institute, 1989)
Papers presented at the Conference on Public Intervention in Farmer-Managed Irrigation Systems, Kathmandu, Nepal, 3-6 August 1986, sponsored by the International Irrigation Management Institute (IIMI) in collaboration with the Water & Energy Commission Secretariat (WECS) of the Ministry of Water Resources of Government of Nepal.